Binary relaxor piezoceramic Pb (Mg1/3Nb2/3) O3-PbTiO3 for energy harvesting - Bhoi, Bomkesh; Purohit, Pranati (International Journal of Advances in Applied Sciences, 2025)
Perovskite relaxor-PT piezoelectrics are suitable materials for energy harvesting. Relaxor-PT crystals have electromechanical properties that can replace lead zirconate titanate (PZT). However, the growth of these relaxor-PT crystals is tedious and expensive. The important parameter for energy harvesting is the transduction rate (d×g) where d represents the piezoelectric coefficient and g represents the piezoelectric voltage constant. There is always a challenge to obtain a high (d×g) value. Lead magnesium niobate Pb (Mg1/3Nb2/3) O3-lead titanate PbTiO3 (PMN-PT) is a binary relaxor-PT ceramic and the morphotropic phase boundary (MPB) of (1-x) PMN-xPT ceramics occur around x=0.29-0.40 which is not exactly defined. So here we have synthesized 0.71PMN-0.29PT, 0.68PMN-0.32PT, and 0.65PMN-0.35PT compositions by two-step sintering solid-state method. The x-ray diffraction (XRD) patterns of the PMN-PT ceramics exhibit a characteristic perovskite structure and also show that PMN-PT ceramics fall within the region of MPB. Out of the three compositions, the 0.71PMN-0.29PT ceramics show a higher transduction rate (d×g). So, this piezoelectric ceramic has the potential to replace costly piezoelectric single crystals in the creation of affordable, high-frequency energy harvesting devices.